Effect of NaOH etching and oxygen plasma treatments on surface characteristics and their potential to activate micro-arc oxidized TiO2 coatings - Costa, Natália A. [UNESP]; Ribeiro, Ana R.; Rossi, André L.; Monteiro, Cláudia; Lisboa-Filho, Paulo N. [UNESP]; Martins, M. Cristina L. (Elsevier, 2025)
Activation treatments such as NaOH etching or O2 plasma can play an essential role in surface conjugation of titanium with biomolecules, providing a better interaction at the bone-implant interface. However, their application on complex titanium dioxide (TiO2) surfaces is still not explored. In this contribution, bioactive and porous TiO2 coatings produced by micro-arc oxidation (MAO) were treated with NaOH etching or O2 plasma and then placed in contact with a reactive isocyanate test compound to evaluate the potential of molecule conjugation. Results suggested that O2 plasma treatment has only changed the surface chemistry of the coating through carbon contaminants removal, plasma-driven oxidation and generation of functional OH species, including reactive carboxyl groups. This chemical modification by plasma has made the surface superhydrophilic. After NaOH etching, the coating became rougher and also superhydrophilic, containing titanate structures doped with sodium and calcium on its surface and inside the inner pores. Upon reaction with butyl isocyanate, the O2 plasma-treated surfaces seem to better provide molecule conjugation, introducing characteristic conjugation bonds, and also making MAO coatings more hydrophobic due to the surface-terminated methyl chains from isocyanate. This proof-of-concept study has demonstrated the promising grafting potential given by O2 plasma on complex TiO2 surfaces.
Keywords: Micro-arc oxidation; Molecule conjugation; NaOH etching; Oxygen plasma; Surface functionalization; Titanium